Aristotle on necessity, chance and explanation - Judson, L (1986)
Aristotle endorses a very striking doctrine connecting necessity with what seems to be a non-modal notion -- that of 'being or happening always'. He also forges a connection between the idea of 'happening by chance' and 'happening neither always nor for the most part'. These two connections form the subject of this essay. My guiding aim is to provide an account of what the 'always/necessary' doctrine involves and of why Aristotle might have held it. Reflection on the nature of the connection between 'by chance' and 'neither always nor for the most part' throws light on what Aristotle means by 'happening always', and, in consequence, on the nature of the link between 'always' and 'necessary'; it also suggests that the basis of this link is to be found in Aristotle's general conception of the natural world as the object of explanation and knowledge. The primary texts upon which discussion of these connections must focus are De Caelo I. 12 and the analysis of chance in Physics II. 4—6. I discuss these two texts in turn, after a opening chapter which surveys the evidence for Aristotle's acceptance of the 'always/necessary‘ doctrine and considers the nature of the restrictions which he places on it. Chapter 2 comprises a translation of and commentary on Cael. I. 12, together with a translation and discussion of its companion chapter, I. 10. In Chapter 3, I examine the nature of Aristotle's argument in I. 12, and criticise various interpretations which see it as evidence that Aristotle's 'always/necessary' doctrine rests on a distinctive conception of possibility. The translation of and commentary on Phys. II. 4-6 (Chapter 4) are followed in Chapter 5 by a discussion of issues relating to the association of chance with 'neither always nor for the most part'. The final chapter returns to the question of the connection between 'always' and 'of necessity'.